2008
DOI: 10.1021/ef800323d
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Thermal Cracking of N-Dodecane in Presence of Several Initiative Additives: Products Distribution and Kinetics

Abstract: Supercritical initiative-thermal cracking of a jet fuel model compound, n-dodecane, was studied in presence of several initiative additives, such as1-nitropropane (NP), triethylamine (TEA), and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane (TEMPO) in view of improving heat sink of jet fuel. It was found that remarkable promoting effect of the initiative additives on the cracking rates, compared with the thermal cracking of pure n-dodecane, were observed up to 20-150% in the following order: NP > TEMPO > T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…These reactions can be due to the thermal fluid decomposition and to the degradation of the material itself. The degree of decomposition is highly dependent on the operating conditions (temperature, pressure, type of flow, nature of reactor) [10,[12][13][14][15]. Thermal cracking of hydrocarbons have been widely studied in petrochemical industry [16][17][18][19][20] and in the context of chemical vapor infiltration for the preparation of carbon/carbon composites [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These reactions can be due to the thermal fluid decomposition and to the degradation of the material itself. The degree of decomposition is highly dependent on the operating conditions (temperature, pressure, type of flow, nature of reactor) [10,[12][13][14][15]. Thermal cracking of hydrocarbons have been widely studied in petrochemical industry [16][17][18][19][20] and in the context of chemical vapor infiltration for the preparation of carbon/carbon composites [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal degradation of the fuel would act as a heat sink before entering in the combustion chamber. The choice of the fuel is critical and numerous studies have been conducted in order to explore the potential of several hydrocarbons [3][4][5][6][7]. The experimental analysis of the distribution of the pyrolyzed products (notably the formation of solid carbon) is one of the fundamental keys of research [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Small amounts of nitroalkanes (R-NO 2 ) serving as soluble initiators have been incorporated into n-alkanes (R'H) which are the major components of endothermic hydrocarbon fuels, [6] and then significant promotion on the overall thermal decomposition was observed. [7][8][9] The thermal decomposition mechanism of hydrocarbons is generally accepted as the free-radical chain reaction. [10,11] The initial step to form free radicals is considered to be the rate-controlling step (crossing the highest activation barrier) in the reaction sequence.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the initial decomposition step of the binary mixture, previous work, however, only attributed the promoting effect to somewhat weaker C-NO 2 bond present in the nitroalkane molecules relative to the C-C bonds within the n-alkane molecules. [7][8][9] On the basis of their incomplete experimental predictions, it is concluded that the C-NO 2 bond can firstly dissociate at relatively low temperatures to produce reactive free radicals compared with the C-C bond rupture of n-alkane, and hence the ensuing decomposition reaction is sustained by the formed free radicals. Accordingly, the initial decomposition route proposed above can be described as follows: R-NO 2 →•R+•NO 2 (1)…”
Section: Introductionmentioning
confidence: 99%